Acceleration of Bone Fracture Healing through the Use of Natural Bovine Hydroxyapatite Implant on Bone Defect Animal Model - Khotib, Junaidi; Lasandara, Cantika SC; Samirah, Samirah; Budiatin, Aniek S (Folia Medica Indonesiana, 2019)
Bone is an important organ for supports the body that stores reserve of calcium, phosphorus, and other minerals. In fracture conditions where bleeding, soft tissue edema, nerve damage, and blood vessels around the bone damage happen, they can cause the mobilization of these minerals in the surrounding tissue. One of the efforts made in the treatment of these fractures is reconnection, in which it works by filling of bone defect with a matrix and administration of anti-infection. Biomaterial filling in defective bone is thought to accelerate the healing process of bone fracture and prevent osteomyelitis. For this reason, this study evaluates the acceleration of bone fracture healing using natural hydroxyapatite (NHA) bone filler in rabbits with bone defect model. Fracture modeling was performed by surgical technique and drilling of bones with a 4.2 mm diameter to form a defect in the rabbit femur. Bone implant contained bovine hydroxyapatite-gelatin-glutaraldehyde (BHA implant) or bovine hydroxyapatite-gelatin-glutaraldehyde-gentamicin (BHA-GEN implant) that was inserted in bone defects. 27 rabbits were divided into 3 groups: the control group who had bone defect, the bone defect group was given BHA implant and the bone defect group was given BHA-GEN implant. Observation of osteoclast, osteoblast, osteocyte, BALP level, and bone morphological integrity was carried out on the 14th, 28th, and 42nd days after surgery. Histological observation of rabbit femur showed a significant difference on the number of osteoclast, osteoblast and osteocyte in all three groups. The BALP level also showed a significant difference in the group given the natural BHA bone implant compared to the control group on day 14 (p = 0.0361). Based on the result of the X-ray, there was also a better integration of rabbit femur bone in groups with the use of BHA or BHA-GEN bone implant. Thus, it can be concluded that the use of a natural BHA implant can accelerate the process of bone repair in the fracture of rabbit femur. In addition, BHA implants were compatible as a matrix for supporting the bone cell growth.